REFLEKSJE NA TEMAT ŻĄDAŃ NIEMCÓW SUDECKICH ANULOWANIA TZW. DEKRETÓW BENESZA - Piotr, Łaski (Wydział Prawa i Administracji UAM, 2004)
The accession of the Czech Republic to the European Union has brought the case of annulment of the so-called Benes decrees to the agenda of German-Czech relations. The decrees were legal acts of the same force as the parliamentary Acts and they were being passed by the Czech emigration authorities since 1942 and signed by E. Beneś, the president of the republic. They were meant to act against the Sudeten Germans inhabiting the inter-war German-Czech frontier. The main thrust of the decrees was to deprive the Sudeten Germans of their property and citizenship as a response to their declaration of allegiance to the Nazi Germany after the capture of the Sudeten Mountains and other parts of Czechoslovakia by the Nazis.
THOUGHTS ON DEMANDS PRESENTED BY THE SUDETEN GERMANS TO NULLIFY THE SO-CALLED BENEŚ DECREES